Anaplastic large cell lymphoma arises in thymocytes and requires transient TCR expression for thymic egress - Tim I. M. Malcolm (Nature Portfolio, 2016)
Anaplastic large cell lymphoma is characterized by an NPM–ALK fusion but the cell of origin for this cancer is unclear. Here, the authors show that, in an NPM–ALK mouse model, the tumours likely arise from early thmyocytes and require an initial burst of TCR signalling for initiation.